Fashion and utopia in management thinking - Bos, René ten (Advances in organization studies ;, 2000)
"Why is it that people in organizations seem to be so vulnerable to management fashion and guruism? And why is it that both phenomena are loathed in traditional academic thinking about management and organization?" "Rene ten Bos argues for a more philosophical rather than scientific understanding of management fashion. In doing so he questions the positivist and utopian orthodoxies that have pervaded management thinking. Ten Bos contends that management fashion is a cultural phenomenon that deserves serious reflection not only because it is so immensely widespread but also because it seems to satisfy particular philosophical needs among its consumers." "Building upon some rather unusual sources in postmodern theory, the author argues that management fashion might encourage the practitioner to engage in philosophical self-examination and to adopt alternative forms of understanding. However, it is also argued that management fashion often fails to keep up to this promise because it remains paradoxically incapable of laying off its rationalist cloak."--Jacket